Blind multi-signature scheme based on factoring and discrete logarithm problem - Duc Nguyen Tan; Hai Nguyen Nam; Minh Nguyen Hieu (Universitas Ahmad Dahlan, 2019)
One of the important objectives of information security systems is providing authentication of the electronic documents and messages. In that, blind signature schemes are an important solution to protect the privacy of users in security electronic transactions by highlighting the anonymity of participating parties. Many studies have focused on blind signature schemes, however, most of the studied schemes are based on single computationally difficult problem. Also digital signature schemes from two difficult problems were proposed but the fact is that only finding solution to single hard problem then these digital signature schemes are breakable. In this paper, we propose a new signature schemes base on the combination of the RSA and Schnorr signature schemes which are based on two hard problems: IFP and DLP. Then expanding to propose a single blind signature scheme, a blind multi-signature scheme, which are based on new baseline schemes.